Inclusion, exclusion, agency, and advocacy : experiences of women with physical disabilities in China, with worldwide implications - Hu, Luanjiao (Transforming education for the future., 2024)
"This book mainly explores the lived experiences of six women, including the author herself, with physical disabilities in China. The book provides in-depth descriptions of each woman's experiences in different aspects and analyze the commonalities and differences in their experiences through their life courses. The book explores answers to some of these questions: How do physically disabled women make sense of their experiences? What are some of the empowering and/or disempowering moments/events in their lives, if any? What are disabled women's experiences in terms of education, employment, relationships, family life, and social activism? How does some of the disabled women in the book become motivated and mobilized to work on disability issues? This book serves to amplify Chinese disabled women's stories and make their presence more visible. Too often, dominant narratives and depictions of disability are written by people without disabilities, while disabled people's voices are either invisible or secondary. Sadly, this phenomenon is not new and disability advocates have been faced with these types of narratives for quite some years. To have one's own voice and speak up is to claim subjectivity, agency, and power. Different stories told by women with disabilities themselves can enrich our understanding of disability and gender. These stories have the potential to challenge dominant and oppressive narratives prevalent in our ableist societies. The stories included in this book could provide space and potential to connect with disabled people (people with either visible or invisible disabilities) elsewhere. Women's empowering experiences and encounters shown in this book could inspire relevant stakeholders to think of ways to better understand and support disabled women in their environments. This book will have wide implications for readers not only in China, but also in other parts of the world. Many disability stories of exclusion and/or empowerment of the world are still hidden and not reflected upon. The author invites readers to reflect on their own experiences and how societies have impacted the life courses of individuals with or without disabilities in their respective social, political, economic, and cultural environments. Cultural and social change around disability can start with anyone who are touched by genuine stories of vulnerability and reflexivity, as the ones to be shared in this book"--